Improving SPDC single-photon sources via extended heralding and feed-forward control - Massaro, Marcello; Meyer-Scott, Evan; Montaut, Nicola; Herrmann, Harald; Silberhorn, Christine (New Journal of Physics)

Characterisation of fabrication inhomogeneities in Ti:LiNbO3 waveguides - Santandrea, Matteo; Stefszky, Michael; Roeland, Ganaël; Silberhorn, Christine (New Journal of Physics)

Fabrication limits of waveguides in nonlinear crystals and their impact on quantum optics applications - Santandrea, Matteo; Stefszky, Michael; Ansari, Vahid; Silberhorn, Christine (New Journal of Physics)

Counter-propagating photon pair generation in a nonlinear waveguide - Luo, Kai-Hong; Ansari, Vahid; Massaro, Marcello; Santandrea, Matteo; Eigner, Christof; Ricken, Raimund; Herrmann, Harald; Silberhorn, Christine (Optics Express)

Nano-architectural complexity of zinc oxide nanowall hollow microspheres and their structural properties - Engelkemeier, Katja; Lindner, Jörg K N; Bürger, Julius; Vaupel, Kathrin; Hartmann, Marc; Tiemann, Michael; Hoyer, Kay-Peter; Schaper, Mirko (Nanotechnology)

Nonlinear optics in all-dielectric nanoantennas and metasurfaces: a review - Sain, Basudeb; Meier, Cedrik; Zentgraf, Thomas (Advanced Photonics)
Free from phase-matching constraints, plasmonic metasurfaces have contributed significantly to the control of optical nonlinearity and enhancement of nonlinear generation efficiency by engineering subwavelength meta-atoms. However, high dissipative losses and inevitable thermal heating limit their applicability in nonlinear nanophotonics. All-dielectric metasurfaces, supporting both electric and magnetic Mie-type resonances in their nanostructures, have appeared as a promising alternative to nonlinear plasmonics. High-index dielectric nanostructures, allowing additional magnetic resonances, can induce magnetic nonlinear effects, which, along with electric nonlinearities, increase the nonlinear conversion efficiency. In addition, low dissipative losses and high damage thresholds provide an extra degree of freedom for operating at high pump intensities, resulting in a considerable enhancement of the nonlinear processes. We discuss the current state of the art in the intensely developing area of all-dielectric nonlinear nanostructures and metasurfaces, including the role of Mie modes, Fano resonances, and anapole moments for harmonic generation, wave mixing, and ultrafast optical switching. Furthermore, we review the recent progress in the nonlinear phase and wavefront control using all-dielectric metasurfaces. We discuss techniques to realize all-dielectric metasurfaces for multifunctional applications and generation of second-order nonlinear processes from complementary metal–oxide–semiconductor-compatible materials.

Engineering integrated photon pair sources and multiplexed detectors (Conference Presentation) - Meyer-Scott, Evan; Prasannan, Nidhin; Montaut, Nicola; Tiedau, Johannes; Eigner, Christof; Harder, Georg; Sansoni, Linda; Nitsche, Thomas; Herrmann, Harald; Ricken, Raimund; Quiring, Viktor; Bartley, Tim; et al. (Advances in Photonics of Quantum Computing, Memory, and Communication XII)

Zinc oxide based dielectric nanoantennas for efficient nonlinear frequency conversion - Golla, C.; Weber, N.; Meier, Cedrik (Journal of Applied Physics)

Strong nonlinear optical response from ZnO by coupled and lattice-matched nanoantennas - Protte, Maximilian; Weber, Nils; Golla, Christian; Zentgraf, Thomas; Meier, Cedrik (Journal of Applied Physics)

Nonreciprocal Asymmetric Polarization Encryption by Layered Plasmonic Metasurfaces - Frese, Daniel; Wei, Qunshuo; Wang, Yongtian; Huang, Lingling; Zentgraf, Thomas (Nano Letters)
As flexible optical devices that can manipulate the phase and amplitude of light, metasurfaces would clearly benefit from directional optical properties. However, single layer metasurface systems consisting of two-dimensional nanoparticle arrays exhibit only a weak spatial asymmetry perpendicular to the surface and therefore have mostly symmetric transmission features. Here, we present a metasurface design principle for nonreciprocal polarization encryption of holographic images. Our approach is based on a two-layer plasmonic metasurface design that introduces a local asymmetry and generates a bidirectional functionality with full phase and amplitude control of the transmitted light. The encoded hologram is designed to appear in a particular linear cross-polarization channel, while it is disappearing in the reverse propagation direction. Hence, layered metasurface systems can feature asymmetric transmission with full phase and amplitude control and therefore expand the design freedom in nanoscale optical devices toward asymmetric information processing and security features for anticounterfeiting applications.

Reconfigurable metasurface hologram by utilizing addressable dynamic pixels - Li, Tianyou; Wei, Qunshuo; Reineke, Bernhard; Walter, Felicitas; Wang, Yongtian; Zentgraf, Thomas; Huang, Lingling (Optics Express)

Silicon metasurfaces for third harmonic geometric phase manipulation and multiplexed holography - Reineke, Bernhard; Sain, Basudeb; Zhao, Ruizhe; Carletti, Luca; Liu, Bingyi; Huang, Lingling; de Angelis, Costantino; Zentgraf, Thomas (Nano Letters)

Metasurface interferometry toward quantum sensors - Georgi, Philip; Massaro, Marcello; Luo, Kai Hong; Sain, Basudeb; Montaut, Nicola; Herrmann, Harald; Weiss, Thomas; Li, Guixin; Silberhorn, Christine; Zentgraf, Thomas (Light: Science & Applications)

High-precision determination of silicon nanocrystals: optical spectroscopy versus electron microscopy - Köthemann, Ronja; Weber, Nils; Lindner, Jörg K N; Meier, Cedrik (Semiconductor Science and Technology)

Simultaneous Spectral and Spatial Modulation for Color Printing and Holography Using All-dielectric Metasurfaces - Wei, Qunshuo; Sain, Basudeb; Wang, Yongtian; Reineke, Bernhard; Li, Xiaowei; Huang, Lingling; Zentgraf, Thomas (Nano Letters)

Four‐Wave Mixing Holographic Multiplexing Based on Nonlinear Metasurfaces - Lin, Zemeng; Huang, Lingling; Xu, Zhen Tao; Li, Xiaowei; Zentgraf, Thomas; Wang, Yongtian (Advanced Optical Materials)

Dynamic control of mode modulation and spatial multiplexing using hybrid metasurfaces - Lin, Zemeng; Huang, Lingling; Zhao, Ruizhe; Wei, Qunshuo; Zentgraf, Thomas; Wang, Yongtian; Li, Xiaowei (Optics Express)

Miniaturized Metalens Based Optical Tweezers on Liquid Crystal Droplets for Lab-on-a-Chip Optical Motors - Suwannasopon, Satayu; Meyer, Fabian; Schlickriede, Christian; Chaisakul, Papichaya; T-Thienprasert, Jiraroj; Limtrakul, Jumras; Zentgraf, Thomas; Chattham, Nattaporn (Crystals)
Surfaces covered with layers of ultrathin nanoantenna structures—so called metasurfaces have recently been proven capable of completely controlling phase of light. Metalenses have emerged from the advance in the development of metasurfaces providing a new basis for recasting traditional lenses into thin, planar optical components capable of focusing light. The lens made of arrays of plasmonic gold nanorods were fabricated on a glass substrate by using electron beam lithography. A 1064 nm laser was used to create a high intensity circularly polarized light focal spot through metalens of focal length 800 µm, N.A. = 0.6 fabricated based on Pancharatnam-Berry phase principle. We demonstrated that optical rotation of birefringent nematic liquid crystal droplets trapped in the laser beam was possible through this metalens. The rotation of birefringent droplets convinced that the optical trap possesses strong enough angular momentum of light from radiation of each nanostructure acting like a local half waveplate and introducing an orientation-dependent phase to light. Here, we show the success in creating a miniaturized and robust metalens based optical tweezers system capable of rotating liquid crystals droplets to imitate an optical motor for future lab-on-a-chip applications.

Strong Nonlinear Optical Activity Induced by Lattice Surface Modes on Plasmonic Metasurface - Chen, Shumei; Reineke, Bernhard; Li, Guixin; Zentgraf, Thomas; Zhang, Shuang (Nano Letters)

Herstellung von Wellenleitern aus Materialien der KTP-Familie - Padberg, Laura; Eigner, Christof; Santandrea, Matteo; Silberhorn, Christine

Efficient C-band single-photon upconversion with chip-scale Ti-indiffused pp-LiNbO3 waveguides - Xie, Zhenda; Luo, Kai Hong; Chang, Kai Chi; Panoiu, Nicolae C.; Herrmann, Harald; Silberhorn, Christine; Wong, Chee Wei (Applied Optics)
Keywords: Atomic and Molecular Physics; and Optics; Engineering (miscellaneous); Electrical and Electronic Engineering

Estimating the Indistinguishability of Heralded Single Photons Using Second-Order Correlation - Faruque, Imad I.; Sinclair, Gary F.; Bonneau, Damien; Ono, Takafumi; Silberhorn, Christine; Thompson, Mark G.; Rarity, John G. (Physical Review Applied)
Keywords: General Physics and Astronomy

Temporally multimode four-photon Hong-Ou-Mandel interference - Ferreri, Alessandro; Ansari, V.; Silberhorn, Christine; Sharapova, Polina R. (Physical Review A)

Spatially asymmetric transients of propagating exciton-polariton modes in a planar CdZnTe/CdMgTe guiding structure - Vondran, J.; Spitzer, F.; Bayer, M.; Akimov, I. A.; Trautmann, Alexander; Reichelt, Matthias; Meier, Cedrik; Weber, N.; Meier, Torsten; André, R.; Mariette, H. (Physical Review B)

Mode-independent quantum entanglement for light - Sperling, Jan; Perez-Leija, Armando; Busch, Kurt; Silberhorn, Christine (Physical Review A)

Experimental Reconstruction of Entanglement Quasiprobabilities - Sperling, Jan; Meyer-Scott, E.; Barkhofen, Sonja; Brecht, Benjamin; Silberhorn, Christine (Physical Review Letters)

Generating two-mode squeezing with multimode measurement-induced nonlinearity - Riabinin, Matvei; Sharapova, Polina; Bartley, Tim; Meier, Torsten (arXiv:1912.09097)
Measurement-induced nonclassical effects in a two-mode interferometer are investigated theoretically using numerical simulations and analytical results. We demonstrate that for certain parameters measurements within the interferometer lead to the occurrence of two-mode squeezing. The results strongly depend on the detection probability, the phase inside the interferometer, and the choice of the input states. The appropriate parameters for maximized squeezing are obtained. We analyze the influence of losses and confirm that the predicted effects are within reach of current experimental techniques.

On the Adsorption of DNA Origami Nanostructures in Nanohole Arrays - Brassat, Katharina; Ramakrishnan, Saminathan; Bürger, Julius; Hanke, Marcel; Doostdar, Mahnaz; Lindner, Jörg; Grundmeier, Guido; Keller, Adrian (Langmuir)
DNA origami nanostructures are versatile substrates for the controlled arrangement of molecular capture sites with nanometer precision and thus have many promising applications in singlemolecule bioanalysis. Here, we investigate the adsorption of DNA origami nanostructures in nanohole arrays which represent an important class of biosensors and may benefit from the incorporation of DNA origami-based molecular probes. Nanoholes with well-defined diameter that enable the adsorption of single DNA origami triangles are fabricated in Au films on Siwafers by nanosphere lithography. The efficiency of directed DNA origami adsorption on the exposed SiO2 areas at the bottoms of the nanoholes is evaluated in dependence of various parameters, i.e., Mg2+ and DNA origami concentrations, buffer strength, adsorption time, and nanohole diameter. We observe that the buffer strength has a surprisingly strong effect on DNA origami adsorption in the nanoholes and that multiple DNA origami triangles with 120 nm edge length can adsorb in nanoholes as small as 120 nm in diameter. We attribute the latter observation to the low lateral mobility of once adsorbed DNA origami on the SiO2 surface, in combination with parasitic adsorption to the Au film. While parasitic adsorption can be suppressed by modifying the Au film with a hydrophobic self-assembled monolayer, the limited surface mobility of the adsorbed DNA origami still leads to poor localization accuracy in the nanoholes and results in many DNA origami crossing the boundary to the Au film even under optimized conditions. We discuss possible ways to minimize this effect by varying the composition of the adsorption buffer, employing different fabrication conditions, or using other substrate materials for nanohole array fabrication.

On the Adsorption of DNA Origami Nanostructures in Nanohole Arrays - Brassat, Katharina; Ramakrishnan, Saminathan; Bürger, Julius; Hanke, Marcel; Doostdar, Mahnaz; Lindner, Jörg; Grundmeier, Guido; Keller, Adrian (Langmuir)

Photonic crystal properties of Si and SiO2 nanopillar arrays fabricated by nanosphere lithography and metal-assisted wet-chemical etching - Kismann, Michael; Riedl, Thomas; Wu, Xia; Wagner, Thorsten; Lindner, Jörg

Strain Relaxation in InAs Nanoislands on top of GaAs (111) A Nanopillars - Riedl, Thomas; Kunnathully, Vinay; Trapp, Alexander; Reuter, Dirk; Lindner, Jörg

MBE Growth of InAs on Nanopillar-Patterned GaAs (111) A - Riedl, Thomas; Kunnathully, Vinay; Trapp, Alexander; Reuter, Dirk; Lindner, Jörg

Impact of shell growth on recombination dynamics and exciton-phonon interaction in CdSe-CdS core-shell nanoplatelets - Achtstein, Alexander W.; Marquardt, Oliver; Scott, Riccardo; Ibrahim, Mohamed; Riedl, Thomas; Prudnikau, Anatol V.; Antanovich, Artsiom; Owschimikow, Nina; Lindner, Jörg; Artemyev, Mikhail; Woggon, Ulrike (accepted 05.09.2018)

Self-assembled Surface Patterns for Controlled Nanoparticle Placement and Improved Semiconductor Heteroepitaxy - Brassat, Katharina; Riedl, Thomas; Lindner, Jörg

Exciton-Phonon Interaction in Core-Only, Core-Shell Nanoplatelets and Quantum Dots - Scott, Riccardo; Prudnikau, Anatol; Antanovich, Artsiom; Christodoulou, Soririos; Riedl, Thomas; Bertrand, Guilaume; Owschimikow, Nina; Lindner, Jörg; Hens, Zeger; Moreels, Iwan; Artemyev, Mikhail; Woggon, Ulrike; et al. (submitted to Nano Letters)

Stability of Heteroepitaxial Coherent Growth Modes on Nanowire Radial Surfaces - Riedl, Thomas; Lindner, Jörg (submitted to Phys. Rev. Mat.)

Modification of block copolymer lithography masks by O2 plasma treatment: Insights from lift off experiments, nanopore etching and free membranes - Brassat, Katharina; Kool, Daniel; Lindner, Jörg (To be submitted)

Nanostructure Research using Transmission Electron Microscopy at the new OWL Analytic Centre - Riedl, Thomas; Bürger, Julius; Kunnathully, Vinay; Wiegand, Marie; Duschik, K.; Ramermann, D.; Ennen, I.; Hertle, Y.; Schaper, Mirko; Hellweg, T.; Hütten, A.; Lindner, Jörg

State-of-the-art transmission electron microscopy in the imaging and scanning mode - Lindner, Jörg

Engineering integrated sources of entangled photon pairs - Meyer-Scott, Evan; Prasannan, Nidhin; Montaut, Nicola; Tiedau, Johannes; Harder, Georg; Sansoni, Linda; Herrmann, Harald; Eigner, Christof; Ricken, Raimund; Quiring, Viktor; Bartley, Tim; Barkhofen, Sonja; et al. (Frontiers in Optics / Laser Science)

Engineering integrated sources of entangled photon pairs - Meyer-Scott, Evan; Prasannan, Nidhin; Montaut, Nicola; Tiedau, Johannes; Harder, Georg; Sansoni, Linda; Herrmann, Harald; Eigner, Christof; Ricken, Raimund; Quiring, Viktor; Bartley, Tim J.; Barkhofen, Sonja; et al. (Frontiers in Optics / Laser Science)

Hierarchical nanopores formed by block copolymer lithography on the surfaces of different materials pre-patterned by nanosphere lithography - Brassat, Katharina; Kool, Daniel; Bürger, Julius; Lindner, Jörg (Nanoscale)
Bottom-up patterning techniques allow for the creation of surfaces with ordered arrays of nanoscale features on large areas. Two bottom-up techniques suitable for the formation of regular nanopatterns on different length scales are nanosphere lithography (NSL) and block copolymer (BCP) lithography. In this paper it is shown that NSL and BCP lithography can be combined to easily design hierarchically nanopatterned surfaces of different materials. Nanosphere lithography is used for the pre-patterning of surfaces with antidots, i.e. hexagonally arranged cylindrical holes in thin films of Au, Pt and TiO2 on SiO2, providing a periodic chemical and topographical contrast on the surface suitable for templating in subsequent BCP lithography. PS-b-PMMA BCP is used in the second self-assembly step to form hexagonally arranged nanopores with sub-20 nm diameter within the antidots upon microphase separation. To achieve this the microphase separation of BCP on planar surfaces is studied, too, and it is demonstrated for the first time that vertical BCP nanopores can be formed on TiO2, Au and Pt films without using any neutralization layers. To explain this the influence of surface energy, polarity and roughness on the microphase separation is investigated and discussed along with the wetting state of BCP on NSL-pre-patterned surfaces. The presented novel route for the creation of advanced hierarchical nanopatterns is easily applicable on large-area surfaces of different materials. This flexibility makes it suitable for a broad range of applications, from the morphological design of biocompatible surfaces for life science to complex pre-patterns for nanoparticle placement in semiconductor technology.

A Novel Lubricant Based on Covalent Functionalized Graphene Oxide Quantum Dots - Wolk, Andreas; Rosenthal, Marta; Neuhaus, Stephan; Huber, Klaus; Brassat, Katharina; Lindner, Jörg; Grothe, Richard; Grundmeier, Guido; Bremser, Wolfgang; Wilhelm, René (Scientific Reports)
Dodecyl amine edge functionalized few-layer graphene oxide quantum dots were synthesized in good yields. The covalent functionalization was demonstrated with NMR and AFM-IR. The resulting structure and particle size was measured with AFM and HRTEM. The thermal stability of the compound was investigated and showed a stability of up to 220 °C. The modified graphene oxide quantum dots showed excellent solubility in various organic solvents, including ethers, methanol, toluene, n-hexane, heptane, xylene, dichloromethane and toluene. The stability of a resulting toluene solution was also proven by static light scattering measurements over several days. The excellent solubility gives the possibility of an efficient and fast spray application of the functionalized graphene oxide quantum dots to steel surfaces. Hence, the macroscopic friction behavior was investigated with a Thwing-Albert FP-2250 friction tester. A thin film of the dodecyl amine functionalized graphene oxide quantum dots on steel lowered the friction coefficient from 0.17 to 0.11 and revealed a significant corrosion inhibition effect.

Easily Accessible Protein Nanostructures via Enzyme Mediated Addressing - Rüdiger, Arne A.; Brassat, Katharina; Lindner, Jörg; Bremser, Wolfgang; Strube, Oliver I. (Langmuir)
Site-specific formation of nanoscaled protein structures is a challenging task. Most known structuring methods are either complex and hardly upscalable or do not apply to biological matter at all. The presented combination of enzyme mediated autodeposition and nanosphere lithography provides an easy-to-apply approach for the buildup of protein nanostructures over a large scale. The key factor is the tethering of enzyme to the support in designated areas. Those areas are provided via prepatterning of enzymatically active antidots with variable diameters. Enzymatically triggered protein addressing occurs exclusively at the intended areas and continues until the entire active area is coated. After this, the reaction self-terminates. The major advantage of the presented method lies in its easy applicability and upscalability. Large area structuring of entire support surfaces with features on the nanometer scale is performed efficiently and without the necessity of harsh conditions. These are valuable premises for large-scale applications with potentials in biosensor technology, nanoelectronics, and life sciences.

With directed self-arrangement of DNA origami to large-area quantum dot arrays - Grundmeier, Guido; Brassat, Katharina; Keller, A.; Lindner, Jörg

Hierarchical nanopore and nanoring arrays by self-assembly techniques - Brassat, Katharina; Kool, Daniel; Lindner, Jörg

Ti-6Al-4V alloy: 3D printing of lightweight implants and nanopatterning by self-assembly - Brassat, Katharina; Taube, A.; Kool, Daniel; Tasche, L.; Hoyer, K.P.; Schaper, Mirko; Lindner, Jörg

Morphology investigation of nanopores by block copolymer lithography on different material surfaces - Brassat, Katharina; Kool, Daniel; Taube, A.; Schaper, Mirko; Lindner, Jörg

Nanoscopic protein arrays on BCP prepatterned surfaces - Brassat, Katharina; Brüngeler, A.; Bremser, W.; Strube, O.I.; Lindner, Jörg

Hierarchical nanopatterns by site-selective DNA origami adsoprtion on pre-patterned surfaces - Brassat, Katharina; Ramakrishna, S.; Keller, A.; Lindner, Jörg